2017
DOI: 10.1007/s15010-017-0989-0
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of blood smear DNA to confirm disseminated histoplasmosis

Abstract: To the best of our knowledge, this is the first case of Hcc infection diagnosed in Senegal. Blood smear may be a valuable screening tool in the case of bloodstream dissemination and can be used for further molecular approaches to confirm the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…capsulatum has yet been reported in Burkina Faso. However, it is important to note that this infection has been reported in several of the surrounding countries [ 36 , 37 ] and probably exists in Burkina Faso. Recently, Mandengue et al suggested that it is likely that a number of cases remain undiagnosed because the clinical presentation may somewhat mimic TB [ 5 ].…”
Section: Discussionmentioning
confidence: 93%
“…capsulatum has yet been reported in Burkina Faso. However, it is important to note that this infection has been reported in several of the surrounding countries [ 36 , 37 ] and probably exists in Burkina Faso. Recently, Mandengue et al suggested that it is likely that a number of cases remain undiagnosed because the clinical presentation may somewhat mimic TB [ 5 ].…”
Section: Discussionmentioning
confidence: 93%
“…36 These superficial and subcutaneous FDs generally have an arsenal of antifungals that permit their management even if the latter treatment sometimes remains probabilistic. 37 For DFDs, the reported publications essentially concern histoplasmosis, 38,39 especially the African form often treated with disappointment, 15 and cryptococcosis with which alternative treatment regimens have been adopted with a success rate estimated at 36.7%. 40 Rare cases of pneumocystosis 41 and aspergillosis/aspergilloma have been reported, treated by surgery without any adjunction of antifungal for the aspergilloses’ management, possibly due to antifungals unavailability.…”
Section: Analysis Of the Burden Of Fungal Diseases In Senegalmentioning
confidence: 99%
“…Common Superficial Tinea capitis Ndiaye et al, 16 Kane et al, 17 Ndiaye et al 18 Onychomycoses Seck et al, 19 Sylla et al, 20 Diongue et al 21 Intertrigos Diongue et al, 22 Ndiaye et al, 23 Diongue et al 24 Pityriasis versicolor, otitis and vulvovaginal candidiasis Dioussé et al, 25 Diongue et al, 26 Dieng et al, 27 Sylla et al 28 Subcutaneous Mycetomas Ndiaye et al, 32 Dieng et al, 33 Sow et al, 34 Badiane et al, 35 Diatta et al 37 Deep Cryptococcosis Sow et al, 40 Diallo Mbaye et al, 45 Manga et al 46 Pneumocystosis Dieng et al 41 Uncommon Superficial keratitis, endodontic candidiasis Ndoye et al, 29 Diongue et al, 30 Ndiaye et al 31 Subcutaneous Chromomycosis Develoux et al 36 Deep Histoplasmosis Ndiaye et al, 14 Diadie et al, 15 Diongue et al, 38 Dieng et al 39 Aspergillosis Ndiaye et al, 42 Ade et al, 43 Ba et al 44 Therapeutic Advances in Infectious Disease 8 4 journals.sagepub.com/home/tai…”
Section: Frequency Mycoses (Fungal Diseases) Authorsmentioning
confidence: 99%
“…Polymerase Chain Reaction (PCR) assay has been widely accepted for detection of reservoirs for H. capsulatum in the environment [43,49]. Bone marrow and blood specimen have high sensitivity especially in patients with disseminated disease but less in immunocompetent [50,51]. Respiratory biopsies and samples have shown good sensitivity [14].…”
Section: Diagnosismentioning
confidence: 99%